Erysiphe elevata causing powdery mildew on Eucalyptus urophylla × E. camaldulensis in China - Yi, Run Hua (Plant disease, 2023)
Eucalyptus urophylla × E. camaldulensis, named Chiwei eucalypt, is a hybrid species widely used in China. Many of its clones are cultivated for afforestation due to cold tolerance, high yield, high strength and disease resistance. Clone LH1 is planted extensively for its high stability and machinability in South China. In December 2021, severe powdery mildew signs were observed on clone LH1 in Zhanjiang, Guangdong (N28°8'29"; E110°17'5"). Whitish powder principally appeared on both abaxial and adaxial leaf surfaces. All plants were infected within about a week and above 90% leaves were diseased, which resulted in abnormal growth and shrinkage of leaves. Hyphae with single, lobed appressoria were hyaline, septate, branched, 3.3-6.8 µm (ave. 4.9 µm, n>50) wide. Conidiophores with a straight to flexuous foot-cell (14.7-46.1×5.4-9.7 µm, ave. 25.8×7.9 µm, n>30) were erect, hyaline, 2-septate, unbranched, 35.4-81.8 × 5.7-10.7 (ave. 56.7×8.7 µm, n>50). Conidia were solitary, hyaline, cylindrical to elliptical, 27.7-46.6 ×11.2-19.0 (ave. 35.7×16.6 µm, n>50). Chamothecia were not found on infected trees. The further identification was confirmed by partial sequences of internal transcribed spacer (ITS), large submit rRNA gene (LSU), Glyceraldehyde-3-phosphate dehydrogenase (GAPDH), glutamine synthetase (GS), and RNA polymerase II second largest subunit (RPB2) gene. A very small amount of mycelia and spores from voucher specimens CCAS-ASBF-1 and CCAS-ASBF-2 were deposited in the herbarium of Guangdong Ocean University. Specimens were PCR amplified and sequenced with primer pairs ITS1/ITS4 (White et al 1990), LROR/LR7 (Moncalvo et al 1995), PMGAPDH1/PMGAPDH3R, GSPM2/GSPM3R and PmRpb2_4/ PMRpb2_6R (Bradshaw, et al. 2022), respectively. BLASTn results showed that ITS (OP270019 and OQ380937), LSU (OP270018 and OQ380938), GAPDH, GS and RPB2 (OQ414445- OQ414450) were above 99% identical with those of E. elevata on Catalpa bignonioides (ITS: AY587013) (Cook et al 2004), Plumeria rubra (ITS: MH985631) (Yeh et al 2019), Cerbera manghas (ITS: MZ379159; LSU: MZ379160) (Mukhtar et al 2022), and Eucalyptus camaldulensis (LSU: LC177375-6) (Meebon et al. 2017), and above 99% identical with those of Erysiphe vaccinii FH00941201 on Vaccinium corymbosum (ITS: ON073869; RPB2: ON119159; GS: ON075687) and FH00112205 on V. vacillans (ITS: ON073870; GAPDH: ON075646) (Bradshaw et al 2022). This is the first sequence data for non rDNA of E. elevata. In an ITS tree phylogenetic analysis with Maximum likelihood (ML) method showed the fungus clustered in a highly supported clade with E. elevata and E. vaccinii. In a multi-locus tree, E. elevata grouped in a sister position to E. vaccinii FH00941201. Thus, the pathogen was identified as E. elevata based on morphology, DNA BLASTn and phylogenetic analysis (Braun and Cook 2012). Pathogenicity tests were conducted on healthy leaves of 1-year-old potted plants. Ten leaves were cleaned with sterile water, inoculated by gently dusting conidia from single lesion on the naturally infected leaves, and then covered with plastic bags containing wet absorbent cotton. Non-inoculated leaves served as controls. Symptoms developed on all inoculated leaves 3 to 5 days after inoculation, and the fungus was identical to the original fungus on the infected leaves, whereas control plants remained symptomless. This is the first report of powdery mildew caused by E. elevata on Eucalyptus sp. from China. This finding is helpful for land managers to diagnose and control the disease